Quality of Elderly\'s Life in Tehran Senile Culture House Clubs - Mahnaz Ahangari; Mohammad Kamali; Manoochehr Arjmand Hesabi (University of Social Welfare & Rehabilitation Sciences, 2007)
Objectives: Today, the rate of aged persons in the world population is rapidly rising. For making decision and planning for this proups, we must know their problems exactly. One way for this purpose is to measure quality of life that it is one of the best criteria in the rehabilitation and health assessment. The objective of this study was to assess, quality of life and the some factors that affect such measures. Methods & Materials: A Cross-sectional conducted and descriptive analytical study which included 300 subjects who were >/=60 years of age chosen randomly. Quality of life assessed, using the whoqol-bref questionnaire with four domains: physical, psychological, social and environmental. Data gathering was done with face to face interview method and the data were analyzed by using t-test, anova and linear regression in spss. Results: Research resulted as mean age 68.08 with sd. Deviation of 5.75 year. Women were (74.33%) 233 and men were (25.66%) 77 of total samples. The final result indicated that there is a significant difference between the mean of qol scores with gender in physical (P<0.001) and psychological (P<0.014) domains. Women had lower qol scores than men. There was significant difference between qol score and age in physical (P<0.036) and psychological (P<0.097) domains too. Widowed persons had lower levels of qol scores than married and singles had better scores in physical domain than the others. Quality of life scores were strongly correlated with educational status and currently ill in all domain scores. Conclusion: Some variables and factors such as illness, level of education marital status, gender and and age affect on quality of life's strategies should be directed toward such variables mentioned for planning, in solving problems is present and future.